Correlation between red blood cell distribution width and cardiovascular events in the patients receiving peritoneal dialysis: A Strobe-compliant article. Issue 6 (February 2019) - Cao, Hui-xia; Zhao, Xin-di; Yan, Lei; Fan, Xiao-guang; Shao, Feng-min
Abstract : Abstract: There are few studies on the correlation between red blood cell distribution width (RDW) and cardiovascular events in the patients receiving peritoneal dialysis (PD). We explored the correlation between RDW and cardiovascular events in PD patients and possible mechanism. A total of 138 PD patients were divided into RDW < 15% group (n = 104) and RDW ≥ 15% group (n = 34). The levels of serum C-reactive protein (CRP) [3.05 (0.79, 15.30) mg/L vs 2.15 (1.00, 6.50) mg/L] and parathyroid hormone (PTH) [260.0 (192.7, 352.6) ng/L vs 200.7 (118.0, 319.7) ng/L] were significantly higher, but the levels of serum albumin [30.65 (27.4, 32.8) g/L vs 32.3 (29.25, 34.95) g/L], prealbumin [(299 ± 96) g/L vs (346 ± 86) g/L], triglyceride [1.24 (0.72, 1.50) mmol/L vs 1.42 (1.12, 1.84) mmol/L], and transferrin saturation [27.9 (16.4, 43.6)% vs 37.8 (23.3, 57.2)%] were significantly lower in the RDW ≥ 15% group than in the RDW < 15% group (all P < 0.05). The RDW was negatively correlated with albumin ( r = − 0.258, P = 0.002), prealbumin ( r = −0.236, P = 0.005), and triglyceride ( r = −0.194, P = 0.023), but was positively correlated with CRP level ( r = 0.174, P = 0.041). The incidence of cardiovascular events was significantly higher in the RDW ≥ 15% group (6 patients, 17.6%) than in the RDW < 15% group (6.7%) (7 patients, P < 0.01). Cox proportional hazard model showed that elevated RDW level was an independent risk factor for cardiovascular events in PD patients (HR = 1.622, 95% CI: 1.063–2.475, P = 0.025). The elevated RDW may be served as a risk factor to predict the cardiovascular events in PD patients.